Medical-scientific knowledge raising in Cartagena de indias - Chajín-Mendoza Osiris María (Revista Ciencias Biomédicas, 2011)
The importance of tracing the origins of acertain discipline in past practices that serve asits inheritance does not come simply from an interest in history. The importance lies inthat, in revising its origin, it is possible to discover that this wasn’t simple, but markedby contradictions. Medical practice isn’t stranger to such situations. In Cartagena, thedevelopment of medical knowledge is linked to significant concerns about urban life,such as public health, social assistance and the recognition of the medical profession,among other topics that are redefined by the force of imaginaries of the progress withthe passage of the 19th century to the 20th century. The aim of this paper is to surveythe rise of the scientific medical knowledge in Cartagena, from a corpus of researchconcerned with the subject, in the context of the historical evolution of the city.RESUMEN:La importancia de rastrear los orígenes de un determinado saber en las prácticas pasadasque le sirven de herencia, no proviene simplemente de un interés por la historia. Laimportancia radica en que, al revisar su origen, es posible descubrir que éste no fuesimple, sino que estuvo signado por contradicciones. La práctica médica no es ajena aeste tipo de situaciones. En Cartagena, el desarrollo del saber médico se vincula conpreocupaciones significativas de la vida urbana, como la higiene pública, la asistenciasocial y el reconocimiento del oficio médico, entre otros temas que se resignifican por lafuerza de los imaginarios del progreso propio del paso del siglo XIX al siglo XX. Nuestroobjetivo en este artículo es revisar el ascenso del saber médico científico cartagenero, através de un corpus de investigaciones preocupadas por el tema en el marco del devenirhistórico de la ciudad.